Evidence for changes in estuarine zooplankton fostered by increased climate variance - Marques, Sónia Cotrim (2020)
Estuaries are among the most valuable aquatic systems in terms of their services to human welfare. They offer an ideal framework to assess multiscale processes linking climate and food web dynamics through the hydrological cycle. Resolving food web responses to climate change is fundamental to resilience management of these threatened ecosystems under global change scenarios. Here, we examined the temporal variability of the plankton food web in the Mondego Estuary, central Iberian Peninsula, over the period 2003 to 2012. The results pointed out a cascading effect from climate to plankton communities that follow a non-stationary behavior shaped by the climate variance envelope. Concurrent changes in hydrographic processes at the regional, that is, upwelling intensity, and local, that is, estuarine hydrology, scales were driven by climatic forcing promoted by the North Atlantic Oscillation; the influence of which permeated the physical environment in the estuary affecting both autotrophic and heterotrophic communities. The most conspicuous change arose around 2008 and consisted of an obvious decrease in freshwater taxa along with a noticeable increase in marine organisms, mainly driven by gelatinous zooplankton. The observed increase in small-sized cosmopolitan copepods, that is, Clausocalanus arcuicornis, Oithona plumifera, thermophilic species, that is, Penilia avirostris, and gelatinous zooplankton suggests a structural change in the Mondego plankton community. These results provide empirical support to the expectation that expanding climate variance changes plankton structure and functioning, likely fostering trophic interactions in pelagic food webs.